Pola Keberislaman Generasi Milenial Manado di era Post-Truth - Rusdiyanto, Rusdiyanto; Gonibala, Rukmina (FIKRAH, 2019)
This paper describes the Islamic practice of Indonesian Muslim student in the digital age. The object of study is Muslim students from three different campuses in Manado. Observations and interviews were conducted to obtain data. There are two important points as a result. First, the trend of the millennial generation in learning and gaining an understanding of Islam is more widely pursued independently through access to information technology. Secondly, the expression of the millennial generation's Islamicism which gained religious understanding with the instant process through the internet made this generation prone to ignore the objective, scientific, and argumentative facts in expressing understanding of Islam, so that their understanding and expression tended to be particular. The presence, convenience, and advancement of information technology have an effect on forming the patterns and religious expressions of the millennial generation.